LONTAR TARU PREMANA WARISAN JENIUS LOKAL BALI KAJIAN ETNOPEDAGOGI - Yudha Satya Dharma; Agung Rai Jayawangsa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
A cultural inheritance must have certain goals and purposes related to its existence. Same with Bali island which is very rich in traditional and cultural heritage. One of the cultural traditions of Balinese people is the culture of lontar writing. Lontar is a note written on palm leaf which is the origin of its naming (rontal). Lontar contains various notes about Balinese culture, in the lontar all forms of information and knowledge that are set forth as notes to be learned and applied in the future by the next generation of Balinese people. From various types of lontar in Bali, the usadalontar is a note included in the traditional health science clump, which consists of various types including usada tumbal, usada punggung tiwas, usada tiwang, usada edan, usada buduh, usada tetenger, usada upas, usada sasah bebai, usada taru pramana and so on. From various types of usadalontars certainly have their techniques and methods controlled in an effort to cure the patient. Lontarusada taru pramana is one of the cultural heritage of Balinese people. As a medical script, of course in the life of the ancestors of the Balinese people, this script was very important in healing people who were sick. lontar taru pramana is a type of medical science that relies on herbal methods which contain notes on various types of herbal medicinal plants and their functions in medicine. Beside of environmentally friendly and at the same time maintaining the balance of the ecosystem of traditional medicinal plants, of course there will not be many side effects for human health in the future. Therefore, it is very necessary to reintroduce traditional medicine to the community, especially to the Balinese people today, who seem to have almost forgotten their ancestral cultural heritage.The lontar taru pramana manuscript consists of the building blocks of the structure itself. The elements that make up the structure in lontar taru premana are characters or characterizations, incidents, plot, themes, and messages. The main character in the lontar taru premana script is Mpu Kuturan because this character is very instrumental in building the story, and always appears in every conversation. The auxiliary or secondary characters in the story contained in the lontar taru pramana text are all plants that are invited to have a dialogue with Mpu Kuturan. The incident in the lontar taru premana manuscript was when Mpu Kuturan lost his ability to care for the sick. The plot that appears in the lontar taru premana script is an interruptedly, where the story in the script develops not only in the main character, namely Empu Kuturan but there are tree figures who help the storyline. The theme in the lontar taru premana script is taru premana, which is the title of the script. Because what is discussed in the lontar premana is about various types of plants in the treatment of an appropriate disease in social life in society. The mandate contained in the lontar taru premana manuscript consists of an implicit and explicit mandate. Implicitly, the message conveyed in the lontar taru premana is that all problems must have a solution. While in explicitly shown by plants which introduce themselves and their functions in medicine.The functions of the taru pramana text among others are for treatment, preserving the environment, welfare for the community, and for religion. The function of medicine is very clear from the contents of the taru pramana text which describes the use of each plant as a medicinal plant. The function of manuscripts in environmental reports can be seen from the impact of the knowledge of traditional medicinal plants. The function in community welfare can be seen from the market for herbal medicines which is able to compete with conventional medicines. In connection with religious functions, it can be seen from the contents of the text of the lontar taru pramana which in the treatment procedure contains prayers or worship to certain gods which are regulated by Balinese Hindus.Reviewed from of the pedagogical aspect, lontar taru premana greatly contributed the effort to introduce traditional medicinal plants to the next generation of Bali. So that for Balinese people, lontar taru premana has a pedagogical meaning in the education of Balinese children in an effort to recognize and apply plants in traditional Balinese medicine. Traditional health can be interpreted as a reference in guiding children to achieve their certain goals.Keywords: Lontar taru premana, Balinese Local Genius, Etnopedagogy.